Estudo das percepções ambientais e de ações educativas promotoras da biodiversidade em unidade de conservação no Rio Grande do Norte - Nascimento, Maria Vitória élida do (2011)
Important issues involving the awakening to the need for conservation of biodiversity and the importance of establishing protected areas as a strategy in pursuit of environmental protection, are increasingly being developed in biological and social investigative fields. In this sense, this research aimed to emphasize the use of environmental perception of social agents are significant elements for the understanding of the man / nature, and develop educational activities aimed at raising awareness and changing attitudes towards environmental issues thus promoting reflections on Environmental Education (EE) as a critical and transformative tool for conservation of rich biological diversity. This research covers as a place of study, schools located in the Environmental Protection Area Jenipabu (APAJ), Rio Grande do Norte. Methodology in general, we highlight the use of questionnaires and mind maps as generators of the contents of empirical research, and execution of content analysis for the treatment of data collected. This dissertation has two chapters in the form of scientific articles, where the first is entitled: "Study of the perceptions and evaluation of interactions concerning environmental education in schools in a conservation area of Rio Grande do Norte - Brazil", obtaining thus a primary diagnosis for analysis about the visions that students and teachers from two schools located in APAJ have on the environment. The second article, entitled: "Effective and analysis of educational activities that promote biodiversity in a coastal area of Environmental Protection Northeast - Brazil" provides an analysis of the educational use of biodiversity as a way to raise awareness of the need for environmental conservation. It appears from research that there is a lack of training in EA by teachers, but there is a need for greater involvement of students in conservation areas, however, from the analysis of educational activities, we observed that the effectiveness of such actions acts to promote awareness and change in actors involved. Thus, environmental education needs to take into account the different perceptions found in each individual, and it can not be based solely on transmission of knowledge, so that we reach a model of conservation.